From Brown to Bakke : the Supreme Court and School Integration: 1945-1978. - Wilkinson, J. Harvie (Oxford University Press, 1989)
Wilkinson's incisive history of the Supreme Court's halting role in integrating education focuses on the two most controversial Supreme Court decisions of this generation and the country's reaction to them.